Effect of Aloe vera gel on wound healing process for diabetic foot ulcers: A pilot study - Malini, Hema; Komela Sari, Yance; Oktarina, Elvi (Gaceta Médica de Caracas, 2022)
Introduction: Patients who experience diabetic foot ulcers (DFU) should have undertaken prompt wound care. Currently, the principles of wound care have shifted to the moist principles of a wide range of treatments, advanced technology, and complementary alternative therapy. This study aimed to investigate the effects of Aloe vera gel therapy as a complementary alternative therapy to promote wound healing of DFU.